«Yo he viajado mucho en mis sueños. Me han llevado por el Atlántico y también por el Amazonas». Territorios oníricos del pueblo indígena kukama - Angulo-Giraldo, Miguel (2026)
This article analyzes the dream narratives of the Kukama indigenous people of the Peruvian Amazon as accounts that reveal cosmological territorial interactions between «peoples» (human and non-human) across the vast Kukama indigenous territory. Challenging the dream-wakefulness dichotomy, the study proposes the concept of «oneiric territory» as a habitable extension where the spirit travels and negotiates with diverse alterities (plant-beings, masters of the land, and ancestors). Through an ethnographic content analysis, the dual dimension of dreaming is examined: first, as a school for acquiring technical and healing knowledge, and second, as a zone of risk characterized by ontological vulnerability to capture or seduction by other entities. The study concludes that dreaming constitutes a space-time where the Kukama being extends their social and cosmological fabric to establish indispensable diplomatic relations with non-humans, visiting both their own territories and new places inhabited by other peoples. These processes of dialogue and cosmological alliances are integral to the ecological-social balance and the constitution of the Kukama personhood.